The EU’s Renewable Energy Directive – Planning and Permitting Under the RED III - Gurreck, Matti (Studia Prawa Publicznego, 2025)
The article examines the recent changes to the EU’s Renewable Energy Directive, in short: RED. In order to accelerate the roll-out of renewable energy, the EU legislator has for the first time introduced spatial planning obligations to the RED and significantly changed the provisions on permitting. Possible conflicts between renewable energy plants, on the one hand, and environmental protection, on the other, should ideally be avoided at the planning stage. In areas designated as Renewable Acceleration Areas (RAAs), renewable energy projects shall be exempt from the requirement to carry out an environmental impact assessment (EIA) pursuant to the EIA Directive (2011/92/EU) and an appropriate assessment of the implications for Natura 2000 sites, according to Article 6(3) of the Habitats Directive. As a result, the reformed Directive prioritises the expansion of renewable energy over nature conservation. In order to fulfil the promise of accelerating the deployment of renewables, open legal questions must be clarified and Member States must use the discretion afforded to them by the Directive. Otherwise, Member State authorities will not be able to implement the measures effectively or risk being caught up in litigation against permits for renewable power plants.